(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This thesis analyzes the semantics of anthroponyms in the English and Uzbek languages from a linguocultural perspective. The study scientifically examines the national-cultural meanings, connotative features, associative fields, and the concept of lexical background in anthroponyms. In addition, the semantic transformation of anthroponyms and their role in expressing cultural codes and national associations are comparatively analyzed on the basis of English and Uzbek materials.